Цитологическая диагностика заболеваний прямой кишки - Лазарев Иван Мефодьевич (Штиинца, 1980)
Экземпляры: КХ (20210910) / Инвентарный номер: 737370 / Сис.шифр: 616.3 / Авт.знак: Л 17 / ГРНТИ: 76 / ББК: 5